2013
DOI: 10.2147/opth.s51774
|View full text |Cite
|
Sign up to set email alerts
|

Changes in retinal nerve fiber layer thickness following mechanical microkeratome-assisted versus femtosecond laser-assisted LASIK

Abstract: PurposeTo study the influence of the transient elevation of intraocular pressure during suction in laser-assisted in situ keratomileusis (LASIK) on the retinal nerve fiber layer (RNFL) thickness both in microkeratome assisted and femotsecond (FS) LASIK.Patients and methodsAn interventional case series that included 40 eyes suffering from myopia who were candidates for LASIK. All underwent Wave Front Guided LASIK by the same surgeon using the VisX CustomVue platform. A corneal flap was created in 20 eyes using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
1
7
0
2
Order By: Relevance
“…In the current study, we attempted to evaluate the effect of applied suction during microkeratome-assisted LASIK on OCT-derived RNFL and macular GC-IPL thickness, in a cohort of myopic patients without any other ocular pathology. According to our findings, suction-induced IOP elevation during LASIK produces nonsignificant alterations on the OCT-derived peripapillary RNFL, which is in agreement with previous literature reports [ 4 , 5 , 16 , 19 , 20 ]. Zhang et al [ 13 ] reported nonsignificant changes in both RNFL and GCC thickness after femtosecond laser-assisted LASIK and femtosecond lenticule extraction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, we attempted to evaluate the effect of applied suction during microkeratome-assisted LASIK on OCT-derived RNFL and macular GC-IPL thickness, in a cohort of myopic patients without any other ocular pathology. According to our findings, suction-induced IOP elevation during LASIK produces nonsignificant alterations on the OCT-derived peripapillary RNFL, which is in agreement with previous literature reports [ 4 , 5 , 16 , 19 , 20 ]. Zhang et al [ 13 ] reported nonsignificant changes in both RNFL and GCC thickness after femtosecond laser-assisted LASIK and femtosecond lenticule extraction.…”
Section: Discussionsupporting
confidence: 93%
“…This was further supported by similar reports, which using SLP with variable corneal compensator concluded that RNFL actually remained unaffected following LASIK, when compensating individually for changes in corneal birefringence [ 17 , 18 ]. In addition, more recent studies utilizing OCT analysis found no LASIK induced peripapillary RNFL alterations [ 4 , 5 , 15 , 16 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported no changes in the peripapillary RNFL thickness. [ 25 26 ] and other researchers reported that the peripapillary RNFL thickness is thinner soon after LASIK. [ 22 27 ] However, a few, rare studies reported changes in the peripapillary RNFL thickness in children.…”
Section: Discussionmentioning
confidence: 99%
“…Данный метод обладает большей точностью, высокой повторяемостью и малой вариабельностью получаемых результатов [25][26][27]. При его использовании в работах, посвященных сравнению способов формирования роговичного клапана (микрокератомом или фемтолазером) при проведении операции ЛАЗИК, стойких изменений ПСНВС выявлено не было [7,10]. Лишь непосредственно после вмешательства (через 30 мин) обнаруживались истончение ПСНВС и утолщение фовеа, которые носили кратковременный характер и уже на следующий день после операции не определялись [10].…”
Section: Discussionunclassified
“…Хорошо известно, что характеристики оптической системы глаза, в первую очередь его длина, могут весьма существенно изменять количественные показатели ОКТ, особенно у лиц с аномалиями рефракции высокой степени [1][2][3][4][5][6]; роль других характеристик менее исследована. В ряде работ изучалось влияние кераторефракционных вмешательств на параметры ОКТ -толщину перипапиллярного слоя нервных волокон сетчатки (ПСНВС) [7][8][9][10], режедругих структур глазного дна [10]. Однако целью большинства этих работ была оценка возможного повреждающего действия кратковременного повышения уровня внутриглазного давления (ВГД) во время операции ЛАЗИК, в том числе в зависимости от способа формирования роговичного клапана (микрокератомом или фемтолазером).…”
unclassified